Relapse Following Allogeneic Hematopoietic Cell Transplantation for Acute Myeloid Leukemia Apparently Due to Somatic Cell Evolution via Epigenetic Variation and Immune Selection - Neil S. Greenspan (Case Western Reserve University, 2019)
In this brief commentary, I discuss a recently published study that documents the role of immune escape in relapse of acute myeloid leukemia (AML) after hematopoietic cell transplantation (HCT). Of particular interest, the mechanism identified by the authors for the ability of the malignant cells to evade destruction by host T cells is the loss of cell surface expression of HLA class II molecules based on processes other than mutation. The authors labeled this mechanism for altered cell surface display of HLA class II antigens "epigenetic."  This study should be of strong interest for immunologists, oncologists and even specialists in infectious diseases for several reasons. First, the results extend the range of examples for which epigenetic mechanisms can play a critical role in resistance to therapy in oncology or infectious disease. Second, findings relating to decreased cell surface display of HLA class II molecules motivate investigation of novel approaches using cytokines to increase the numbers of HLA class II proteins on malignant myeloid cell membranes and reduce the extent of immune escape by these cells. Third, the data presented suggest experimental directions intended to clarify detailed molecular mechanisms underlying the cases of AML post-HCT relapse and raise questions relating to why some mechanisms of somatic cell evolution and not others are operative in different clinical settings.